The Apachetas of the travellers. the contributions of Elena Altuna to the contemporary Andean and Hispanic American colonial studies - Campuzano, Betina Sandra (2021)
It is my aim to focus on a number of notions and categories, which emerge from the critical-theoretical journey of Elena Altuna whose fields of research were the Peruvian colonial culture and the contemporary Spanish-American literature. I will start from the underlying readings in her production which are evidence of the intellectual field and the paradigm shifts of her time. Then, I will advance toward some notions, starting from the notion of foreignness, which copes with the colonial figure, by linking it with the Cornejo-Polarian proposal. Another one is remoteness which, in response to the connections between peninsular and creole people, exposes macerated presentations in colonial writing. Rhetoric of reparation is a notion used to refer to those writing strategies which, far from the mimesis with the metropolis, expose the re-signification of both, the foreign and own traditions in the creole context. The last one is the notion of urban indian, which deals with changes between the indigenist novel and the migrant’s testimony in the literary system. Finally, I will focus on the way in which the constellation of notions that contribute to conform a yachay quipi (Mamani Macedo, 2019), or localized knowledge, is configured.